New Potential Demulsifiers Obtained by Processing Gossypol Resin - Nurlybek Shyrynbekuly Otarbaev; Vladimir Mikhailovich Kapustin; Kazim Sadykovich Nadirov; Gulmira Zhankabylovna Bimbetova; Manap Kurmanbekovich Zhantasov; Rashid Kazimovich Nadirov (Universitas Gadjah Mada, 2019)
Water contained in crude oil, forms so-called water-in-oil emulsions, the presence of which negatively affects the transportation and processing of oil. Demulsifiers are the special mixtures that are used to remove water from emulsions. The present paper is devoted to obtaining the demulsifiers by catalytic acid esterification of fatty acids mixture extracted from gossypol resin with isopropanol. Fourteen mixtures, containing mainly fatty acids and their ethers, were obtained and tested for demulsifying performance by using the bottle test. The relationship of the following values with the demulsibility of final mixtures was determined: the conditions of fatty acids esterification, the content of fatty acids in the demulsifier, the relative solubility number of the demulsifier, the toluene/water dynamic interfacial tension. The following conditions of fatty acids mixture esterification provided 64.8% of water removal at the dosage of 20 ppm of demulsifier: 385 K; 4 h; H2SO4/fatty acids mixture ratio 2.5 wt.%.